RANCANG BANGUN MULTIMEDIA PEMBELAJARAN KERAGAMAN BUDAYA MELALUI WARISAN BUDAYA INDONESIA DENGAN METODE HANNAFIN & PECK - Halda Salsabila; Teuku Mufizar; Cepi Rahmat Hidayat (JEIS: Jurnal Elektro dan Informatika Swadharma, 2025)
Indonesia is rich in diverse cultures, including traditional weapons, dances, houses, clothing, and musical instruments. According to social studies teachers, students are well-acquainted with the cultural heritage of West Java; however, their knowledge of cultures from other provinces remains limited. To address this, a researcher developed an interactive learning media showcasing the cultural diversity of Indonesia's 34 provinces. Each province features five cultural heritages: traditional weapons, dances, houses, clothing, and musical instruments. The learning approach integrates audio, animations, images, and text to engage students more effectively, aiming to foster interest in traditional cultures and ensure their preservation. The application was designed using the Hannafin and Peck model, which comprises three main phases: needs assessment, design, development, and implementation. The study involved seventh-grade students from SMPN 13 Tasikmalaya. Student comprehension was assessed through pretests and posttests, resulting in an N-Gain score of 0.47, which falls into the "Moderate" category. These evaluations indicate that the cultural diversity application is suitable for use as an educational learning medium.Indonesia kaya akan budaya yang beragam contohnya senjata tradisional, tarian tradisional, rumah adat, pakaian adat, dan alat musik tradisional. Menurut guru IPS, siswa sudah banyak mengenal warisan budaya Jawa Barat, akan tetapi dari luar Jawa Barat masih banyak yang kurang mengenal. Oleh sebab itu peneliti menciptakan media pembelajaran interaktif keragaman budaya dari 34 provinsi, di setiap provinsinya terdapat 5 warisan budaya yaitu senjata tradisional, tarian tradisional, rumah adat, pakaian adat, dan alat musik tradisional. dengan cara belajar yang menarik dengan menggabungkan suara, animasi, gambar, dan teks. Dengan begitu, anak-anak Indonesia jadi lebih tertarik mempelajari budaya tradisional, sehingga budaya kita tetap hidup dan terjaga Perancangan aplikasi ini menggunakan metode Hannafin And Peck. Subjek penelitian ini yaitu siswa kelas VII SMPN 13 Tasikmalaya. Pengujian pada penelitian ini menggunakan, pengujian pemahaman siswa yaitu dengan pemberian pretest dan posttest dan N-Gain yang didapat yaitu sebesar 0.47 dalam arti masuk kedalam kritea “Sedang”. Dari pengujian tersebut menghasilkan bahwa aplikasi keragaman budaya melalui warisan budaya Indonesia layak digunakan sebagai media pembelajaran.